(untitled) (Zaporizhzhia Historical Review, 2021)
The main reasons and features of development of contraband trade of the Southern Ukraine in the last quarter of XVIII and the beginning of XIX centuries, the main peculiarities of the struggle against smuggle contraband and effectiveness of governmental activities in this field were elucidated.